UI/UX Design of Mobile-Based Human Resource Management Applications Using the Design Thinking Method (Study Case: Habibi Garden) - Ucha Aprilia; Nia Kumaladewi; Abdul Mutholib; Amart Sulong (Applied Information System and Management (AISM), 2024)
Habibi Garden is a company operating in agricultural technology. The current issue at Habibi Garden is the absence of a human resource management application. COOs and Agronomists face operational challenges. COOs struggle to track project progress in the field and sometimes forget to log their attendance. Agronomists have difficulty organizing team tasks as some employees forget to submit assignments, and various assignments, reports, and projects are jumbled in Google Drive. Additionally, employees have to search for reimbursement links mixed with other assignment links, leading to potential errors. This research aims to develop a UI/UX design for a mobile-based human resource management application for Habibi Garden to aid employees in operational activities. The method used is Design Thinking which consists of 5 stages, namely Empathize, Define, Ideate, Prototype, and Test. The results show that the interface design performs well. The effectiveness parameter scored 93.75% for COOs and 91.25% for Agronomists. The efficiency parameter achieved 0.04 goals/sec for COOs and 0.06 goals/sec for Agronomists. User satisfaction, measured using the SUS questionnaire, averaged 88 for COOs, categorized as excellent and graded B, and 77 for Agronomists, categorized as good and also graded B. Design Thinking enables designers to create application solutions that truly fit user expectations and needs by understanding user problems, needs, and behavior through the empathize stage. Based on the prototype design that has been designed in this study, the UI/UX generated can serve as a foundation for the development of mobile applications based on Human Resource Management.